PENETAPAN UKURAN SASARAN SEBAGAI USAHA PENINGKATAN EFISIENSI PROSES PENGGERGA.JIAN DI LIMA KILANG PENGGERGAJIAN - Osly Bachman; Syarlf Hidayat (Jurnal Penelitian Hasil Hutan, 1991)
nlri•t a.  Is  ou   of  the factors that determine aawin6 efficiency. Tlls objectiue of thit dudy   wa  to provide the lnfonnatlon  on the •wmlllfnl  e('ficMney in 80me    Indonaian  •wmillt.   The  data for the analy.U  were• from 8 •wmilk In  Central .llUll and 2 •wmllla  In .limbL  Ou   hundred board• from each •wmlll   were randomly tuleen to evaluate the uariition of  the tlaiclenna within and betroeen t~   board•, and to determine the deviation of the board  tlaicleu•  from the ,.,,.,    ,,_  in each •wmlll.'f1ae  tlaicleJllla  between the board•  waa fQund to be more •riable   compared with the tlaicle,..,, within the board&. EllfJJthoulla tlN laf61aat deviation of  the board• found In tlaia atudy  wa• llelow PPKGRI atandard,  ..,,.ation    waa made •lam ro minlmlH tlaiclenaadeviation, and the po•ible  lmprouement and maintenance of the aetwork.